Nanotechnology : an introduction - Ramsden, Jeremy (Micro and nano technologies series, 2011)
This book provides an overview of the rapidly growing and developing field of nanotechnology, focusing on key essentials, and structured around a robust anatomy of the subject. The newcomer to nanotechnology, who may well have a strong background in one of the traditional disciplines such as physics, mechanical or electrical engineering, chemistry or biology, or who may have been working in microelectromechanical systems (MEMS) technology, is confronted with a bewildering range of information. This book brings together the principles, theory and practice of nanotechnology, giving a broad yet authoritative introduction to the possibilities and limitations of this exciting field. Succinct chapter summaries allow readers to grasp quickly the concepts discussed and gain an overview of the field Discusses design and manufacture, and applications and their impact in a wide range of nanotechnology areas An ideal introduction for businesses and potential investors in nanotechnology